Can leading a physically active and healthy lifestyle prevent gaining the freshman 15? - Jonathan R. Anderson; Myra J. Bloom; Wyatt T. Broshous; Gladys Y.X. Chen; Scarlet R. Jost; Andrew S.I.D. Lang; Luiz Carlos L.D.S. Neto; Nancy V. Mankin; Erika R. McMahan; Jonathan A. Merheb; Philip P. Nelson; Enrique F. Valderrama-Araya (Termedia Publishing House, 2023)
Purpose The purpose of this study is to investigate if leading a physically active and healthy lifestyle can prevent the weight gain typically experienced during the freshman year of college - the 'Freshman 15'. Methods Study participants ( N = 525) were from three cohorts of incoming students (2018-2020) at a mid-sized university in the West South-Central United States. The weight of each study participant was measured at three points over a year: beginning of their first semester, beginning of their second semester, and beginning of their third semester. During the study, students were encouraged to lead physically active and healthy lifestyles and to exercise daily. Weight changes at sixth months and one-year intervals were recorded as percentages. Results Freshmen weight gain/loss depended upon initial weight with freshmen who arrived on campus with relatively lower weights (≤100 kg) tending to gain weight, especially males, whilst freshmen who arrived on campus with relatively higher weights (≥100 kg) tended to lose weight. This finding was both more apparent and more statistically significant at the 1-year mark than at the 6-months mark. Conclusions Several previous studies have linked freshmen weight gain to initial weight with students with higher initial weights gaining the most. However, our results show that maintaining a physically active and healthy lifestyle when entering college reverses this trend - with students with high initial weights losing weight. Thus, living a physically active and healthy lifestyle, which includes aerobic exercise, can prevent the fat mass weight gain often experienced by college freshmen.